Literature Review: The Relationship Between Servant Leadership and Organizational Culture Development in Educational Institutions - Norma N. Monigir; Suiling Pontoh; Maria Wihelmina Kaparang; Victor Nomel Kumajas (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2024)
This article discusses the relationship between servant leadership and the development of educational organizational culture. Servant leadership, which focuses on serving others, is believed to shape an organizational culture that supports values such as cooperation, open communication, and empowerment of organizational members. In the context of education, the application of servant leadership can improve teacher performance, student motivation, and create an environment conducive to innovation and professional development. This study shows that servant leadership plays an important role in building an inclusive and adaptive organizational culture, which ultimately contributes to improving the quality of education. The results of this literature review emphasize the importance of serving education leaders to encourage collaboration, build respectful relationships, and create an atmosphere that supports individual development in educational institutions. Thus, the application of servant leadership in educational institutions can improve the quality and effectiveness of education as a whole.